Persepsi Masyarakat Terhadap Keterlibatan Perempuan dalam Struktur Pemerintahan Desa Gunung Manaon Kecamatan Panyabungan, Mandailing Natal (Perspektif Gender) - Norma Hanisah Nasution; Efi Brata Madya (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
This study aims to analyze public perception of women's involvement in the government of Gunung Manaon Village, Panyabungan District, Mandailing Natal Village, through a gender perspective with a descriptive qualitative method. The results show that although quota policies open up formal access for women, their participation in decision-making is still hampered by patriarchal norms, gender stereotypes, and biased communication. Some women have begun to participate actively, especially those who have access to education, technology, and social organizations, but this involvement is still limited and not fully supported by the surrounding environment. This study recommends participatory communication strategies, leadership training based on Islamic values, and strengthening the role of the media and community leaders in shaping public opinion that supports gender equality. An integrated approach between affirmative policies and women's capacity building is expected to create a village political climate that is inclusive, fair, and responsive to the needs of all residents regardless of gender.